HEALTHY LIFESTYLE: THE CURRENT STATE OF THE PROBLEM (American Journal of Research in Humanities and Social Sciences, 2024)
A healthy lifestyle is a person’s way of life with the aim of preventing diseases and promoting health. Health is our wealth, which can only be preserved with the right lifestyle. How interesting and colorful his life will be depending on the physical and spiritual state of a person. With a healthy lifestyle, a person can form and improve his well-being by eating right, doing physical exercise and hardening, and rationally organizing his work and rest schedule.